THE INFLUENCE OF COOPERATIVE LEARNING MODEL OF STUDENT TEAM ACHIEVEMENT TYPE ON LEARNING LANGUAGE OUTCOMES - Suci Andriyani; Ruri Rizhardy; Hermansyah (Esteem Journal of English Education Study Programme, 2024)
It is crucial for primary school kids to study Indonesian in order to enhance their overall educational experience. In addition, learning Indonesian can help kids connect with friends and teachers more easily and enhance the standard of instruction provided in the classroom.The purpose of this study is to ascertain whether the cooperative model of the Student Team Achievement Division has an impact on the learning outcomes for Indonesian language for students in class V of SD Negeri 68 Palembang. This study's methodology is quantitative and use saturated sampling techniques in a quasi-experimental fashion. The adoption of the student team achievement divisions type cooperative learning model has a substantial impact on the outcomes of class V Indonesian language learning at SD Negeri 68 Palembang, according to the data analysis and study discussion results. Based on the conducted research, it has been determined that classes receiving treatment and those not receive treatment had different outcomes when it comes to learning the Indonesian language. The experimental class had an average score of 85.57, while the control class had an average score of 77.62. An Independent T Test was used, with sig (2 tailed) 0.000 0.05 or and control class, to determine how the two classes compared.